Formation and controlling of Type-D inclusions in bearing steel - LI Ming; WANG Xin-cheng; DUAN Jia-heng; YANG Wen; CHENG Gong; WANG Lei; YANG Li-wei; ZHANG Li-feng (工程科学学报)
There are strict requirements for non-metallic inclusions in bearing steel, especially for Type-D inclusions.To analyze the formation mechanism of Type-D inclusions in high-frequency detection defects of GCr15 bearing steel bar sample in domestic steel plant and give the effective controlling measure, the inclusion evolution in bearing steel production process before and after optimization was investigated by ASPEX automatic scanning electron microscope.The results show that, the main formation mechanism of calcium aluminate Type-D inclusions present in the original process includes two aspects:one is the high basicity of refining slag, resulting in the high Ca O activity in slag.The other is the strong stirring in vacuum degassing (VD) process, providing good kinetic conditions for slag-steel reactions.The bearing steel production process is optimized from the basicity of refining slag and the vacuum degree of VD process.After optimization, the inclusions change from calcium aluminate to spinel type, and the formation of Type-D inclusions in bearing steel is reduced.Meanwhile, the high cleanliness of bearing steel is maintained.